Gq-Mediated Arrhythmogenic Signaling Promotes Atrial Fibrillation - Felix Hohendanner; Ashok Prabhu; Nicola Wilck; Verena Stangl; Burkert Pieske; Karl Stangl; Till F. Althoff (Biomedicines, 2023)
Background: Atrial fibrillation (AF) is promoted by various stimuli like angiotensin II, endothelin-1, epinephrine/norepinephrine, vagal activation, or mechanical stress, all of which activate receptors coupled to G-proteins of the Gαq/Gα11-family (Gq). Besides pro-fibrotic and pro-inflammatory effects, Gq-mediated signaling induces inositol trisphosphate receptor (IP3R)-mediated intracellular Ca2+ mobilization related to delayed after-depolarisations and AF. However, direct evidence of arrhythmogenic Gq-mediated signaling is absent. Methods and results: To define the role of Gq in AF, transgenic mice with tamoxifen-inducible, cardiomyocyte-specific Gαq/Gα11-deficiency (Gq-KO) were created and exposed to intracardiac electrophysiological studies. Baseline electrophysiological properties, including heart rate, sinus node recovery time, and atrial as well as AV nodal effective refractory periods, were comparable in Gq-KO and control mice. However, inducibility and mean duration of AF episodes were significantly reduced in Gq-KO mice—both before and after vagal stimulation. To explore underlying mechanisms, left atrial cardiomyocytes were isolated from Gq-KO and control mice and electrically stimulated to study Ca2+-mobilization during excitation–contraction coupling using confocal microscopy. Spontaneous arrhythmogenic Ca2+ waves and sarcoplasmic reticulum content-corrected Ca2+ sparks were less frequent in Gq-KO mice. Interestingly, nuclear but not cytosolic Ca2+ transient amplitudes were significantly decreased in Gq-KO mice. Conclusion: Gq-signaling promotes arrhythmogenic atrial Ca2+-release and AF in mice. Targeting this pathway, ideally using Gq-selective, biased receptor ligands, may be a promising approach for the treatment and prevention of AF. Importantly, the atrial-specific expression of the Gq-effector IP3R confers atrial selectivity mitigating the risk of life-threatening ventricular pro-arrhythmic effects.